Protection System Design of Induction Motor for Industries. (31st August 2022) - Shaikh, Shoaib; Kumar, Dileep; Hakeem, Abdul; Soomar, Arsalan Muhammad
Abstract : The fundamental and durable structures of induction motor, as well as their low manufacturing cost, make them popular components in a wide range of current applications. Providing a safety net for employees is a must-have for businesses. This project's motivation for improvement is to provide industrial motors, lift motors, pumps, and so on with safety. An induction motor's primary goal is to protect it from problems, such as single phasing and overheating, as well as other issues. Providing industrial motors, pumps, lift motors, and other similar devices with security is a major motivation behind the emergence of this issue. Any of the three phases missing or the motor temperature above the predetermined threshold causes the motor to stop instantly. Three one-stage transformers are connected to a three-phase power supply in the system. Power will be cut to the transformer circuit if any phase is available. Motors can be turned off by relays sending a signal to the four-pole contactor. As a result, the motor's three-phase power supply has been cut off. Temperature readings are taken from a thermistor (DHT22) that is attached to the motor. At higher temperatures, the three-phase supply will be cut off by a four-pole contactor, and the motor will shut off. This manuscript resolves the uses transformers to solve the problem of single phasing. Also, our project addresses the issue by using microcontroller. It senses all the three phases and decides whether to supply power to induction motor or to disconnect. It deals with the temperature problem, and it uses a thermistor to disconnect the circuitry, whereas in our project, a microcontroller senses the overwhelming temperature and acts accordingly, i.e., give a signal and then move towards disconnection.